Burn Care in the Greek and Roman Antiquity - Christoph Wallner; Eric Moormann; Patricia Lulof; Marius Drysch; Marcus Lehnhardt; Björn Behr (Medicina, 2020)
The last century brought about more rapid new developments in the treatment of burns, which significantly lowered the mortality of burn injuries. However, burns were already treated in antiquity, where the threshold from spirituality to scientific medicine originated. The existing literature on burn treatment is very limited and there are many cross-references, some of them incorrect. The aim of this work by an interdisciplinary team of historians and physicians is to offer a more precise reproduction of the burn treatment of Greek and Roman antiquity using original texts in context and with a modern scientific background. There are many sources from ancient doctors on the subject of burn treatment, as well as the treatment of burned-out wounds and frostbite, which have not yet been mentioned. The literature research also showed an understanding of scientific contexts in ancient medicine, such as antiseptics or rheology. Interestingly, there was a change in burn medicine from everyday Greek medicine to Roman military medicine with other burn patterns. The care of patients using analgetics and the therapy of burn shock arose from the literature. The ancient world is considered to be the foundation of medicine, but it is believed to have been based mainly on shamanism rather than science. However, already more than two millennia ago, burns were correctly assessed and treated according to today’s scientific standards and scientific relationships were recognized.